Peranan Lembaga Ekonomi Islam Aspek Kajian Sejarah Sosial Politik Ekonomi - Naurid Muhammad Rifa’I; Ilyasa Nur Izzati (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2023)
The history of the development of Islamic Shari'a since the time of the Prophet Muhammad, is not only focused on the theological cleansing mission. However, Islamic law has become a universal law in running the wheel of life, one of which is the economy. Where the economy, is one of the characteristics of humans as intelligent creatures of God. In addition, the economy becomes a measure of the level of social status in society. During the da'wah of the Prophet Muhammad, it was recorded that the application of Islamic Sharia in the economy was regulated by establishing the Baitul Maal. Baitul Maal literally means a house to collect or store wealth. In addition, Baitul Maal functions as an institution or party that has a special task of handling all the assets of the people, both in the form of state revenues and expenditures. Thus, the concept of Baitul Maal as an Islamic economic platform is the beginning of the long history of cooperatives and banking based on Islamic law. The history of Islam in the context of economic development, and financial management, did not stop until the time of the da'wah of the Prophet Muhammad. However, it continued during the da'wah of Khulafah Al-Rasyidin (a leader who was guided by Allah SWT). It was during the leadership of Khulafah Al-Rasyidin that the Islamic government had a presidential system from 632-661 AD. Likewise, running the People's Economic Institution, which in this case is accommodated by Baitul Mal, continues to experience administrative development. It was during the time of Khulafah Al-Rashidin that economic administration and financial management based on Islamic Sharia began to be revolutionized until the government changed from the presidential term of Khulafah Al-Rashidun to the Moranki Government which began with the establishment of the Umayyad Dynasty. In fact, not only in the Islamic kingdoms of the Middle East, Islamization through the fields of Economics and Finance became one of the effective ways of da'wah in the archipelago until the establishment of the unitary state of the Republic of Indonesia today Abstrak Sejarah perkembangan Syariat Islam sejak zaman Rasulullah SAW, bukan hanya terpaku pada misi pembersihan secara Teologi saja. Namun Syariat Islam menjadi sebuah hukum yang universal dalam menjalankan roda kehidupan dimana salah satuanya adalah perekonomian. Dimana perekonomian, merupakan salah satu ciri manusia sebagai mahluk tuhan yang berakal. Selain itu perekonomian menjadi sebuah ukuran tindak tanduknya tingkat status sosial di masyarakat. Dimasa dakwah Rasulullah SAW, tercatat penerapan Syariat Islam dalam perekonomian diatur dengan cara mendirikan Baitul Maal. Secara harfiyah Baitul Maal, berarti rumah untuk mengumpulkan atau menyimpan harta. Selain itu, Baitul Maal berfungsi sebagai lembaga atau pihak yang mempunyai tugas khusus menangani segala harta umat, baik berupa pendapatan maupun pengeluaran negara . Dengan begitu, konsep Baitul Maal sebagai wadah perkonomian yang bersyariat Islam, merupakan sebab awal dari sejarah panjang koperasi dan perbankan yang berlandaskan syariat Islam. Sejarah Islam dalam konteks perkembangan ekonomi, dan manajemen keuangan, tidak berhenti sampai dimasa dakwah Rasulullah SAW saja. Namun, terus berlanjut dimasa dakwah Khulafah Al- Rasyidin (pemimpin yang mendapat petunjuk Allah SWT). Dimasa kepemimpinan Khulafah Al- Rasyidin lah, pemerintahan Islam bersistem presidensial sejak 632 – 661 M. Begitupun menjalankan Lembaga Perekonomian umat yang mana dalam hal ini diwadahi oleh Baitul Mal, terus mengalami perkembangan secara administratif. Dimasa Khulafah Al- Rasyidin lah, administrasi ekonomi dan manajemen keuangan berdasarkan Syariat Islam mulai direvolusi sampai bergantinya pemerintahan dari presidensial masa Khulafah Al- Rasyidin menuju Pemerintahan Monarki yang diawali dengan berdirinya Dinasti Umayah. Bahkan bukan hanya dikerajaan Islam Timur Tengah saja, Islamisasi melalui bidang Ekonomi dan Keuangan menjadi salah satu jalan dakwah yang efektif di Nusantara hingga berdirinya negara kesatuan republik Indonesia sekarang ini